Discovery and characterization of a small‐molecule enteropeptidase inhibitor, SCO‐792. Issue 5 (4th September 2019) - Sasaki, Masako; Miyahisa, Ikuo; Itono, Sachiko; Yashiro, Hiroaki; Hiyoshi, Hideyuki; Tsuchimori, Kazue; Hamagami, Ken‐ichi; Moritoh, Yusuke; Watanabe, Masanori; Tohyama, Kimio; Sasaki, Minoru; Sakamoto, Jun‐ichi; et al.
Abstract: Enteropeptidase, localized into the duodenum brush border, is a key enzyme catalyzing the conversion of pancreatic trypsinogen proenzyme to active trypsin, thereby regulating protein digestion and energy homeostasis. We report the discovery and pharmacological profiles of SCO‐792, a novel inhibitor of enteropeptidase. A screen employing fluorescence resonance energy transfer was performed to identify enteropeptidase inhibitors. Inhibitory profiles were determined by in vitro assays. To evaluate the in vivo inhibitory effect on protein digestion, an oral protein challenge test was performed in rats. Our screen identified a series of enteropeptidase inhibitors, and compound optimization resulted in identification of SCO‐792, which inhibited enteropeptidase activity in vitro, with IC50 values of 4.6 and 5.4 nmol/L in rats and humans, respectively. In vitro inhibition of enteropeptidase by SCO‐792 was potentiated by increased incubation time, and the calculated K inact /KI was 82 000/mol/L s. An in vitro dissociation assay showed that SCO‐792 had a dissociation half‐life of almost 14 hour, with a calculated k off rate of 0.047/hour, which suggested that SCO‐792 is a reversible enteropeptidase inhibitor. In normal rats, a ≤4 hour prior oral dose of SCO‐792 effectively inhibited plasma elevation of branched‐chain amino acids in an oral protein challenge test, which indicated that SCO‐792 effectively inhibited protein digestion in vivo. In conclusion, our new screen system identified SCO‐792 as a potent and reversible inhibitor against enteropeptidase. SCO‐792 slowly dissociated from enteropeptidase in vitro and inhibited protein digestion in vivo. Further study using SCO‐792 could reveal the effects of inhibiting enteropeptidase on biological actions.